Pengenalan Aksara Bali Melalui Metode Kolase Sebagai Implementasi Kurikulum Merdeka Belajar dan Merdeka Bermain Pada Anak Usia Dini - Wiguna, Ida Bagus Alit Arta; Ekaningtyas, Ni Luh Drajati; Widari, Ni Made Sinta (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Community service activities focus on Geria Danendra kindergarten by implementing programmes that have been adapted to the conditions in the field. The programme that has been implemented is the introduction of Balinese script. The purpose of introducing Balinese characters is to make early childhood to know that there are Balinese characters as the mother tongue of the ethnic Balinese tribe in the Kuranji Village area, the methods used are lecture methods and collage methods with a scientific approach. The strategy applied in this service is a strategy that focuses on child learning given a collage project. The result of this service is that children are able to complete the picture and collage the picture and know the reading of the collaged characters.